Self-Serving Behavior in Price-Quality Competition - Daniel Halbheer; Marco Bertini; Oded Koenigsberg (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Managers like to think well of themselves, and of the firms that employ them. However, positive illusions can bias a manager's evaluation of market outcomes, self-servingly crediting success on the superior quality of one's own product but blaming failure on the aggressive price of a competitor's offering. These distorted attributions stem from the idea that product quality better serves the manager's motivation for self-enhancement and self-presentation than price: product quality is seemingly more central to the firm, less susceptible to external market forces, and more stable over time. We position our theory in the psychology of attribution, define self-serving behavior and provide experimental and survey evidence of this phenomenon, and develop a model of price-quality competition that incorporates the empirical findings. In particular, we first study the natural benchmark equilibrium provided by unbiased decision makers. We then introduce self-serving behavior in the presence of myopic principals, or of forward-looking principals who anticipate the limitations of managers and set first-period decisions accordingly.
Keywords: L21; M21; M31; 330